¿Entre dos mares? Reflexiones a partir de la Historia Atlántica y hacía tres conceptos de la Historia Global - Bethany Aram (Centre de Recherches sur les Mondes Américains, 2019)
A recent outpouring of scholarship in global history invites reflection on methodological transfers from Atlantic history and, in particular, discussion of the different concepts or types of global history pursued today. The new typology proposed for global history highlights lessons learned in the Atlantic that can be carried beyond it and extended across the Isthmus of Panama and to other crucial routes of early globalization. The heuristic need to differentiate between global and world history is also considered.